Foodborne urinary tract infections: a new paradigm for antimicrobial-resistant foodborne illness - Nordstrom, Lora; Liu, Cindy M.; Price, Lance B. (Frontiers in Microbiology, 2013)
Urinary tract infections (UTIs) are among the most common bacterial infections worldwide. Disproportionately affecting women, UTIs exact a substantial public burden each year in terms of direct medical expenses, decreased quality of life, and lost productivity. Increasing antimicrobial resistance among strains of extraintestinal pathogenic E. coli challenges successful treatment of UTIs. Community-acquired UTIs were long considered sporadic infections, typically caused by the patients’ native gastrointestinal microbiota; however, the recent recognition of UTI outbreaks with probable foodborne origins has shifted our understanding of UTI epidemiology. Along with this paradigm shift come new opportunities to disrupt the infection process and possibly quell increasing resistance, including the elimination of nontherapeutic antimicrobial use in food-animal production.